Reducing stress and promoting social integration of international medical students through a tandem program: results of a prospective-program evaluation - Herrmann-Werner, Anne; Junne, Florian; Stuber, Felicitas; Huhn, Daniel; Nikendei, Christoph; Seifried-Dübon, Tanja; Zipfel, Stephan; Erschens, Rebecca (International journal of environmental research and public health, 2018)
Medical students, and especially international medical students (IMS), have been shown to experience more psychological distress than the general student population in Germany. In order to address these issues, a structured Tandem Program (TP) to reduce stress and foster social integration of IMS has been introduced at the Medical Faculty of Tuebingen. The Tandem Program was evaluated prospectively with perceived stress (PSQ-20) as the main outcome. Secondary outcomes were ‘motives to participate’ in the TP, ‘specific stressors’, and ‘experiences made’ during the program. Stress levels of IMS at the beginning of the program (t0) (M = 48.14, SD = 11.95) were higher than those of German participants (M = 39.33, SD = 8.31) (t (67) = −3.66, p < 0.001). At the end of the TP (t1), stress levels of international students were significantly lower than at t0. “Improved ability to work in a team” was seen as one of the most beneficial factors. The results indicate that tandem programs at medical faculties may be a promising curricular intervention towards reducing stress levels, improving integration of international students, and to enhance intercultural and team-oriented competencies in both international and national medical students.
Published: 7 September 2018
Gesehen am 19.12.2019